Glucagon-Like Peptide-1 Receptor Agonists in Obesity Management: Mechanisms, Efficacy, and Safety - Stasiak, Michał; Żyro, Wiktor; Woźniak, Karolina; Żyro, Katarzyna; Glapiński, Franciszek; Woźniak, Adam (Quality in Sport, 2025)
Obesity remains a major global health challenge with limited pharmacological options that combine efficacy and long-term safety. Traditional anti-obesity drugs, targeting energy expenditure and appetite, often present significant cardiovascular and neuropsychiatric risks. In contrast, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have emerged as promising agents due to their dual benefits of glycemic control and weight reduction. GLP-1, an enteroendocrine hormone, enhances insulin secretion, suppresses glucagon release, and modulates appetite via central pathways. By binding to receptors in the hypothalamus and brainstem, GLP-1 RAs promote satiety, delay gastric emptying, and modulate reward-related eating behaviors, thereby reducing caloric intake. Meta-analyses of randomized controlled trials have demonstrated significant body weight reductions in both diabetic and non-diabetic individuals, with semaglutide showing particularly robust outcomes compared to liraglutide and exenatide. Beyond weight loss, GLP-1 RAs improve insulin sensitivity, lipid profiles, and cardiovascular risk factors. However, their use is associated with gastrointestinal side effects such as nausea, vomiting, and diarrhea, which can affect treatment adherence. While concerns about potential impacts on pancreatic and thyroid tissues have been raised, current large-scale studies do not confirm a causal relationship. Overall, GLP-1 RAs represent a significant advancement in obesity pharmacotherapy by integrating appetite suppression, delayed gastric emptying, and metabolic improvements. Continued research is needed to further optimize their clinical application and ensure long-term safety in obesity management.